1964
DOI: 10.1139/y64-035
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Effect of Bovine Growth Hormone on Blood Sugar of Houssay Dogs

Abstract: A highly purified growth hormone preparation (Wilhelmi) was tested for its hypoglycemic activity in four fasting, hypophysectomized–depancreatized dogs (Houssay dogs) maintained without exogenous insulin for 2–4 weeks. A single intravenous injection of growth hormone, 5 mg per kg body weight, had no effect on blood sugar over a period of 6 hours. It was concluded that highly purified growth hormone has no hypoglycemic effect in the absence of biologically active insulin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

1967
1967
1978
1978

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…were hypophysectomized by the transbuccal technic as described. 4 Previous experiments from this laboratory have shown that little difference exists in the composition of aorta between the ages of six and eighteen months in mongrel dogs of either sex. 5 Completeness of the hypophysectomy was checked by histological examination of the removed tissue and by postmortem examination of the sella turcica.…”
Section: Methodsmentioning
confidence: 96%
“…were hypophysectomized by the transbuccal technic as described. 4 Previous experiments from this laboratory have shown that little difference exists in the composition of aorta between the ages of six and eighteen months in mongrel dogs of either sex. 5 Completeness of the hypophysectomy was checked by histological examination of the removed tissue and by postmortem examination of the sella turcica.…”
Section: Methodsmentioning
confidence: 96%
“…4 animals served as normal con trols and 24 were hypophysectomized by the transbuccal technique as described [16]. Completeness of the hypophysectomy was checked by histological examination of the removed tissue and by postmortem examination of the sella turcica.…”
Section: Methodsmentioning
confidence: 99%
“…Mongrel dogs of either sex, weighing approximately 10 kg each, were hypophysectomized by the transbuccal approach in pentobarbital (Nembutal) anesthesia (35 mg/kg) under aseptic conditions (3). Completeness of the hypophysectomy was checked by histo logical examination of the removed tissue and by postmortem examination of the sella turcica.…”
Section: Methodsmentioning
confidence: 99%